Proletarii vsekh stran i vse trudyashchiyesya! Ob"yedinyaytes' dlya bor'b'í protiv podzhigateley voyny! Za mir, za sotsializm! - Keil, Aleksandr Ivanovich (ОГИЗ - ИЗОГИЗ (Izogiz), 1936)
Left side of poster: Red Army soldier with rifle and tank brigade in front, air force in background. Right side of poster: Red Army soldier Original title: Пролетарии всех стран и все трудящиеся! Обь "идиняйся для того, чтобы ты боролся против поджигателей воюны! За мир, за социализм!. Suggested translation: Proletarians of all countries and all working people! Unite to fight against the warmongers! For peace, for socialism! PO-0008